Respuesta :

Answer:

shown below

Step-by-step explanation:

we know right triangle formula that a² + b² = c²

where  a is opposite, b is adjacent and c is hypotenuse

so, here a = (x + 6) , b  = (x -1) , c = (2x + 1)

(x + 6)² + (x -1 )² = (2x + 1)² ............simplify

x²+12x+36 + x² -2x +1 = 4x² + 4x +1 ...............collect terms

2x² + 10x+ 37 = 4x² + 4x +1  ...............add them

-2x² + 6x + 36 = 0  ................bring them to one side and subtract and add

-2(x²-3x-18) = 0  .........take -2 as coefficient

x²-3x-18 = 0 ...........our final result

Therefore shown that x²-3x-18 = 0

Hey there mate ;),

Let's crack this question now!

Given: x²-3x-18=0

So,

[tex](2x + 1)^{2} = (x + 6)^{2} + (x - 1)^{2} [/tex]

[tex] = > 4 {x}^{2} + 4x + 1 = {x}^{2} + 12x + 36 + {x}^{2} - 2x + 1[/tex]

[tex] = > 4 {x}^{2} + 4x + 1 = 2 {x}^{2} + 10x + 37[/tex]

[tex] = > 4 {x}^{2} - 2 {x}^{2} + 4x - 10x + 1 - 37 = 0[/tex]

[tex] = > 2 {x}^{2} - 6x - 36 = 0[/tex]

Now, by taking 2 as common factor, we get:-

[tex] = > {x}^{2} - 3x - 18 = 0[/tex]

ACCESS MORE